Rising Crude Prices’ Impact – To understand the impact of the volatility of crude oil market over the Singapore economy and also on the Singapore oil companies - Ooi, Ee Sun (2009)
Recent economic and geopolitical events have significantly impacted the crude oil prices worldwide with US crude reaching record highs above $78 dollars per barrel on July 14, 2006. Although the consequences and transmission mechanisms of oil price shocks have been investigated to some extent for developed economies, the impact volatility and rise of oil price on developing countries and emerging market economies (EMEs) have yet to be explored. Established in 1969, Singapore Petroleum Company Ltd (SPC) has become one of the lead players in the local oil industry of Singapore. SPC provides its services in the areas of oil and gas exploration, refining, terminalling and distribution, marketing and trading of crude and refined petroleum products and is the only independent oil refiner in Singapore. Like the rest of the world, the impact of volatility in crude oil prices, SPC has also impacted significantly by swings in refining margins which arise from the interplay of demand and supply for crude oil and refined products. This study aimed at exploring the impact of volatility of crude oil prices on the Singaporean economy in general and particularly on the Singapore oil companies. For this purpose, the meta-analysis method was utilized in order to explore and examine the relevant data and research on the topic and perform a meta-analysis of this data. Data on crude oil, volatility in oil prices and its influence on crude oil companies in Singapore were researched. The research criteria covered the period from 1995 to data and examined the trends in oil markets of USA, Gulf States and the Singapore Petroleum Company Ltd (SPC). First of all, the mechanism of crude oil prices was examined which revealed that in the late 1980s, price formulas were adopted to set export prices. This involved use of three indices for sales of Middle Eastern crudes to various regions: West Texas Intermediate for sales to the US, Brent for sales to Europe, and a combination of Dubai and Oman for sales to the Asia- Pacific region. In general, marker crude would fulfill certain implicit criteria in that it should be a good representative of all the alternative crudes available to buyers in the region in terms of gravity and sulfur content, produced in significant volumes, and should be liquid, i.e., significantly traded in the physical market. However, such mechanism is not going to be sustained for long due to the fact that an increasing need to cut costs by the Asian refiners would result in the need for more competitive deals. Furthermore, the increasing trend of imports of Atlantic Basin crudes (which are priced off Brent) into Asia-Pacific countries may further pressure Middle Eastern producers to reduce, if not remove, the Eastern Premium. Being a small economy Singapore is a price taker in global trade, that is why, fluctuations in crude oil prices have powerful effects on the economy.